Halide effects on the performance of equimolar choline halide: guanidinium thiocyanate deep eutectic solvents as dye-sensitized solar cell electrolytes. Issue 3 (3rd July 2022) - Boogaart, Dustin J.; Essner, Jeremy B.; Baker, Gary A.
ABSTRACT: We have characterized the deep eutectic solvent (DES) comprising a 1:1 equimolar mixture of choline chloride and guanidinium thiocyanate ('guaniline–Cl'), alongside its halide counterparts wherein the bromide or iodide salts of choline are paired with guanidinium thiocyanate ('guaniline–Br' and 'guaniline–I'), as electrolytes for solar photoconversion. These pared-down electrolyte systems containing only DES (up to 90 wt. %), water (up to 40 wt. %), and the I – /I3 – redox couple were explored within dye-sensitized solar cells. Average device performance generally increased with a decrease in hydrogen bond affinity (Cl – < Br – < I – ), with guaniline–I yielding markedly higher photocurrents relative to guaniline–Cl and guaniline–Br. Indeed, 70 and 80 wt. % guaniline–I exceeded power conversion efficiencies of 2.0% despite producing lower photovoltages and fill factors than the corresponding Cl/Br-based electrolytes. Attributed in part to solution viscosity, this effect arises chiefly from the fact that guaniline–I contains substantial organic iodide built into the DES proper. Significantly, this self-contained electrolyte can function as the sole iodide source for forming the required electrolyte redox couple, yielding performance essentially equivalent to lower-viscosity electrolytes containing supplemental inorganic iodide, in spite of significant differences in solution viscosity. GRAPHICAL ABSTRACT: UF0001